The Efficacy of Pramipexole, a Dopamine Receptor Agonist, as an Adjunctive Treatment in Treatment-Resistant Depression: An Open-Label Trial - Hiroaki Hori; Hiroshi Kunugi (The Scientific World Journal)
Dopaminergic dysfunction is implicated in the pathophysiology of treatment-resistant depression. Although the efficacy of adjunctive pramipexole treatment has been demonstrated in treatment-resistant bipolar depression, such data are scarce for major depressive disorder (MDD). We recruited 17 patients with DSM-IV major depressive episode who have failed to respond to previous treatment with a selective serotonin reuptake inhibitor. Five patients were diagnosed as having bipolar II disorder and 12 as having unipolar MDD. Patients were monitored at an ambulatory care facility every two weeks until 12 weeks. Pramipexole was added to existing medication. Depression severity was assessed with the Hamilton Depression Rating Scale 21-item version (HDRS-21). The mean maximum dosage of pramipexole was 1.6 mg (SD 0.9). The HDRS-21 total score decreased from 19.4 (SD 3.8) at baseline to 7.2 (SD 5.4) at endpoint (P<0.000001). Twelve patients (71%) were responders based on the definition of 50% or more reduction in the HDRS-21 score. Ten patients (59%) remitted (HDRS-21 total score at endpoint <8). These results were almost unchanged when the sample was confined to patients with MDD. No serious adverse events were observed. Our findings indicate that pramipexole augmentation therapy may be effective and well tolerated in refractory depressed patients.